2020
DOI: 10.4055/cios19143
|View full text |Cite|
|
Sign up to set email alerts
|

Poor Functional Outcome in Patients with Voluntary Knee Instability after Anterior Cruciate Ligament Reconstruction

Abstract: Anterior cruciate ligament (ACL) tears are commonly seen injuries in sports traumatology. 1) Arthroscopic ACL reconstruction (ACLR) is considered the standard of care for patients with ACL tears with instability. 2-4) The aim of ACLR is to restore the preinjury level of function, which is a challenging task. 5,6) The good functional outcome after ACLR depends upon multiple factors, which can be divided into extrinsic and intrinsic factors. 7) The extrinsic factors include the type of graft used, surgical techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
(25 reference statements)
0
13
0
1
Order By: Relevance
“…They found that 28 of 29 (97%) knees exhibited a positive Lachman test, and the average of differential laxity according to the TelosTM device (Telos Medical, Austin and Associates, Millersville, MD, USA) was 8.3 mm (range, 5 to 13 mm). Anterior instability can be seen in ACL-deficient knees, and >5 mm of anterior tibial translation is generally considered as a cut off value for ACL reconstruction [ 19 , 20 ]. However, two patients underwent subsequent ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 28 of 29 (97%) knees exhibited a positive Lachman test, and the average of differential laxity according to the TelosTM device (Telos Medical, Austin and Associates, Millersville, MD, USA) was 8.3 mm (range, 5 to 13 mm). Anterior instability can be seen in ACL-deficient knees, and >5 mm of anterior tibial translation is generally considered as a cut off value for ACL reconstruction [ 19 , 20 ]. However, two patients underwent subsequent ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, interest and participation in sports and other physical activities among females in South Korea has been lower than those in Western countries. However, women’s engagement in sports in South Korea has recently increased, and this may explain the recent increase of PCLR among Korean women [ 17 , 18 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing meniscal resection may have di culty regaining previous motion abilities. [19,20] Therefore, preventing meniscus aging is one of the treatment strategies to reduce the incidence of meniscus tearing. Through probing the DGIdb website, we selected the above hub genes for molecular docking analysis in order to ascertain potential drugs that could act on these genes (Figure .…”
Section: Construction Of Ppi Network and Hub Genes Analysismentioning
confidence: 99%